Small-scale farmers and land care workers’ perceptions of land degradation and how it influences their livelihoods : an explorative study in Ladybrand - Lombard, A. (Antoinette) (University of Pretoria, 2022)
Dissertation (MA (Social Work))--University of Pretoria,2021.